Rock and drugs: multiliteracies and an aesthetics of violence for teenagers in school (Acta Scientiarum. Language and Culture, 2014)
Current study discusses an approach of hard rock, in English, for high school students, from a multimodal perspective. The songs are analyzed in terms of their musicality and literariness and hard rock is considered a historically constituted complex cultural movement. The aesthetics of violence, present in the rock’n’roll scenario, specifically focused on the themes of drugs and alcohol abuse, is analyzed from the perspective of multiliteracies, for the development of teenagers’ critical education. The paper is theoretically based on theory by Lévy (2010), Kress (2000) and Kalantzis and Cope (2000) for multiliteracy concepts and on Walser (1993) for the criticism on the musical language. Songs by the USA rock bands Metallica and Guns N’Roses are discussed.